The Development of Reading Textbook Oriented to Character Education using Multimodality in College - Sesmiyanti Sesmiyanti; Rindilla Antika; Suharni Suharni (AL-ISHLAH: Jurnal Pendidikan, 2021)
This research aims to develop a textbook for the Basic Reading subject by using multimodality and oriented to character education. This research is research and development, which refers to the ADDIE model (Analysis, Design, Develop, Implementation, and Evaluation). Subjects of this research are students and lecturers who have taken part in the Basic Reading subject at English Education Department STKIP PGRI Sumatera Barat. Data collection techniques used are document analysis, questionnaire, interview, and expert judgments. The results of need analysis show that the textbook used in Basic Reading subject has not oriented to character education and used multimodality yet. The development of Basic Reading has been validated by education experts and practitioners (lecturers). Based on the validation of experts and practitioners, this textbook is included in the very well category and confirmed as the feasibility to use. The trial results in implementing the book show that the N-Gain calculation shows 0.43, which is categorized as moderate, which means the book improves students’ cognitive learning outcomes in the reading subject and also instills core ethical values in daily living. Thus, this textbook is feasible to be used in the learning process at Basic Reading Subject.